The Problem of Independent Curriculum's Application in the students of Grade 1 at SDN 04 Pasar Ambacang, Padang - Rizky Fadhilah, Jihan; Syaida Oktira, Yona; Andri Putra, Dion (The Future of Education Journal, 2022)
This study aims to analyze the implementation and problems of the independent curriculum for grade 1 students at SDN 04 Pasar Ambacang, Padang city. This study uses a descriptive qualitative approach. This research was conducted at SDN 04 Pasar Ambacang, Padang city in July 2022. The data collection techniques used were observation, interviews and documentation studies. The results showed that the implementation of the independent curriculum at SDN 04 Pasar Ambacang had been applied to students in grades 1, where currently the teacher's guidelines for implementation are student textbooks and independent curriculum manuals. In its implementation there are several obstacles in the form of adjusting the application of the independent curriculum which is sometimes still mixed with the previous curriculum, Lack of references in the application of the independent curriculum, Lack of teacher experience on the concept of independent learning. The solution in overcoming these problems certainly requires cooperation from various parties, especially the government as a policy maker, namely by providing training for teachers, and habituation of independent curriculum learning so that it can run according to its focus and objectives.